Hepatoprotective Effect of the Penthorum Chinense Pursh Extract against the CCl4-Induced Acute Liver Injury via NF-κB and p38-MAPK PATHWAYS in Dogs - Weilai Tao; Xin Yue; Ruiling Ye; Fazul Nabi; Yangfei Shang; Zhaorong Zhu; Bhutto Zohaib Ahmed; Juan Liu (Animals, 2022)
Acute liver injury (ALI), manifested by acute hepatocellular damages and necrosis, is a life-threatening clinical syndrome and Penthorum Chinense Pursh (PCP) is a well-known folk medicine practiced for liver-related diseases. This study aimed to investigate the ameliorative effects of PCP extract (PCPE) on carbon tetrachloride (CCl4) induced ALI in dogs via mitogen-activated protein kinase (MAPK) and Nuclear factor κB (NF-κB) signaling pathway. Healthy dogs were induced by CCl4 and treated with different dosage regimes of PCPE for 7 days. CCl4 produced acute liver injury and induced both oxidative stress and an inflammatory response in dogs. The PCPE significantly ameliorated and improved vacuolar inflammatory lesions in liver tissues during ALI, enhanced activity of superoxide dismutase, and restored glutathione peroxidase, further significantly reducing the indices of malondialdehyde and nitric oxide in serum. Inflammatory factors (IL-1β, IL-6, and TNF-α) were declined and anti-inflammatory factors (IL-10) were increased by the application of PCPE. PCPE treatment, down-regulated the MEKK4, MKK3, p38MAPK, MSK1, and NF-κB, and upregulated the IkB mRNA levels (p < 0.01) in ALI affected dogs. In conclusion, PCPE repaired acute liver injury by improving antioxidant enzymes and by reducing oxidation products. Furthermore, the PCPE inhibited the MAPK/NF-κB signaling pathway, which resulted in anti-inflammatory and antioxidant effects on ALI-induced dogs. In the future, PCPE could be a useful ethnomedicine in veterinary clinical practices for the treatment of liver injuries or failures.